2020
DOI: 10.36469/jheor.2020.13457
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Weight Change in People with HIV-1 After Initiating Integrase Strand Transfer Inhibitors or Protease Inhibitors

Abstract: Background: Studies have shown an increase in weight among people living with human immunodeficiency virus (PLWH) who have also initiated integrase strand transfer inhibitors (INSTI). However, limited data are available regarding comparison of these changes with other antiretroviral regimens. Objective: To assess differences in weight gain after initiating INSTI- versus protease inhibitor (PI)- based regimens among treatment-naïve PLWH overall, and among a subpopulation of females only. Methods: This retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…6,7 These findings are consistent with previous clinical and real-world studies reporting increased weight or BMI within approximately 1 year of initiating ARV, and greater weight gain with INSTIs vs other regimens, especially among females and African Americans. 20,22,[27][28][29] In a recent real-world study of treatment naïve PLWH, Chen et al reported a higher risk of 5% weight gain for INSTI vs. PI initiators among the overall study population (1.3 kg greater mean weight gain for INSTI) and among females (2.5 kg greater weight gain for INSTI). 29 A similar real-world study using a different database reported a higher risk of 5% weight gain for INSTI vs. PI initiators overall (1.5 kg greater weight gain for INSTI), but the differences did not reach statistical significance among females, perhaps due to smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 These findings are consistent with previous clinical and real-world studies reporting increased weight or BMI within approximately 1 year of initiating ARV, and greater weight gain with INSTIs vs other regimens, especially among females and African Americans. 20,22,[27][28][29] In a recent real-world study of treatment naïve PLWH, Chen et al reported a higher risk of 5% weight gain for INSTI vs. PI initiators among the overall study population (1.3 kg greater mean weight gain for INSTI) and among females (2.5 kg greater weight gain for INSTI). 29 A similar real-world study using a different database reported a higher risk of 5% weight gain for INSTI vs. PI initiators overall (1.5 kg greater weight gain for INSTI), but the differences did not reach statistical significance among females, perhaps due to smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
“…20,22,[27][28][29] In a recent real-world study of treatment naïve PLWH, Chen et al reported a higher risk of 5% weight gain for INSTI vs. PI initiators among the overall study population (1.3 kg greater mean weight gain for INSTI) and among females (2.5 kg greater weight gain for INSTI). 29 A similar real-world study using a different database reported a higher risk of 5% weight gain for INSTI vs. PI initiators overall (1.5 kg greater weight gain for INSTI), but the differences did not reach statistical significance among females, perhaps due to smaller sample size. 30 In a pooled analysis of 8 clinical trials, Sax et al reported approximately 1.5 kg greater mean weight gain for INSTIs vs. PIs, with female and African Americans/Black patients having greater risk of ≥10% weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior evidence also suggest that weight gain has been observed in the year following initiation of ART [ 10 , 11 ], sometimes as early as 3 months after treatment initiation [ 9 ]. ART-related weight gain also does not affect all PLWH equally, as certain demographic groups, including female, Black and Hispanic PLWH, are generally at greater risk of ART-related weight gain [ 10 , 12 , 13 ], particularly following initiation of INSTI-based regimens [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] To our knowledge, studies regarding ARV therapy in weight gain had different results. [11,16,17] PI therapy was associated with weight gain in some studies. [1,11,18] Todd et al reported PI drugs were not associated with overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%